Bone: The growing cost of fractures in Ireland - Edwards, M; Cooper, C (2012)
Trend analyses reveal an increase in the absolute number of hospitalizations for fragility fractures in Ireland in the past decade, and further increases are projected to occur up to 2025. The economic consequences of this trend must be closely monitored to inform future policy and resource allocation. © 2012 Macmillan Publishers Limited. All rights reserved.